Flooded with data and information - Calderón-Rehecho, Andoni (Anuario ThinkEPI, 2016)
Reflection on the current situation characterized by the existence of huge amounts of data and information. Some aspects such as privacy, data protection, social impact of the technologies, disintermediation, trends, future of libraries, etc., are discussed.